"GENDER REPRESENTATION IN ELT TEXTBOOK: ENGLISH FOR TENTH GRADERS (CONTENT ANALYSIS)" - Fauzi, Khozin; Asih, Yuni Utami; Suhatmady, Bibit (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Gender representation and gender roles have been characterized in a variety of elements based on categories of Gender visibility and Gender roles theory, including Main Characters, Named as Non-active Characters, Non-named, Non-active Characters, Appearances in Illustration, Noun and Pronoun. As a result, the goal of this study was to discover gender representation and gender roles in the English textbook Bahasa Inggris When English Comes in Handy for Tenth Graders. Grafindo Media Pratama is the publisher. The research approach is a qualitative investigation with content analysis. Males dominated in areas such as the number of named-non active, non-named-non active, appearance in drawings, and titled & named, according to the findings of this study. In addition, female characters dominated the primary characters. Males also performed the majority of gender duties, including home and public gender roles. Finally, if the discrepancies between male and female gender are greater than 5%, the book is deemed to possess gender bias, according to Stockdale's thesis.